A hot water-proof plastic film agent, preparation method and application in paper mold manufacturing

Through a new method of plastic film preparation, the problem of existing plastic film agent affecting mechanical properties and waterproof properties in pulp molding is solved, which achieves higher strength, stiffness and overall stability, and improves the long-term Storage stability.

CN119194901BActive Publication Date: 2025-02-18山东奥赛新材料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411707217.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

When used in pulp molded products, although existing plastic film agents can improve waterproof performance, they will affect the mechanical properties, resulting in poor strength and stiffness. At the same time, poor combination performance will reduce waterproof performance after long-term use or storage. .

Method used

A new method of preparing plastic film agent for heat-proofing water penetration is adopted to form plastic films with higher stability and weather resistance through the preparation of reaction substrates, enhancement modifiers, aldehyde grouping and hyperbranching treatment. and more effectively combine with pulp molding materials to form a dense crosslinking network to improve waterproofing performance.

Benefits of technology

It effectively avoids the influence of plastic film agent on the mechanical properties of pulp molding, improves the strength and stiffness of pulp molding, and at the same time enhances the combination performance of plastic film agent and pulp molding materials, improves overall stability, and improves the Long-term storage stability of plastic film agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a hot water-resistant plasticizer, a preparation method and an application in paper mold manufacturing, and belongs to the field of plasticizers. The preparation method of the hot water-resistant plasticizer comprises the following steps: preparing a reaction base material, preparing a drop liquid, and contacting a reaction. The hot water-resistant plasticizer of the present invention can effectively avoid the influence of the plasticizer on the mechanical properties of the pulp molding while avoiding the pulp molding from dropping chips and effectively improving the waterproof performance of the pulp molding, further improving the strength and stiffness of the pulp molding; at the same time, improving the bonding performance of the plasticizer with the pulp molding material, improving the overall stability of the pulp molded product; and further improving the long-term storage stability of the plasticizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of film-forming agents, in particular to a film-forming agent resistant to hot water penetration, a preparation method and application of the film-forming agent in paper mold manufacturing. Background Art

[0002] As people's living standards improve and the pace of work accelerates, the consumption of disposable fast food containers is huge, especially fast food boxes made of expanded polystyrene as the main raw material, which are widely used. However, plastic products made of this type of material are almost impossible to be naturally decomposed or recycled. Discarded fast food boxes can be seen everywhere, causing serious environmental pollution. Environmental pollution has been a common concern of society in recent years. The development of environmentally friendly biomass materials has become the main direction of the current green packaging industry. As one of the ideal choices for replacing petroleum-based packaging materials, pulp molded products have received widespread attention in current research.

[0003] Pulp molding is a three-dimensional papermaking technology that uses primary or secondary plant fibers as raw materials. It has the advantages of abundant reserves, recyclability, no environmental pollution, and natural degradation. It is widely used in fast food tableware, food industry cushioning packaging and other fields. Among them, fast food tableware includes: lunch boxes, dinner plates, dinner bowls, paper cups, etc.; food industry cushioning packaging includes: egg trays, fruit trays, food cushioning trays, etc. The specific pulp molding preparation process usually uses bagasse pulp and bamboo pulp as raw materials. After pulping, grinding, slurry mixing and other processes, it goes through vacuum filtration molding, hot pressing drying and shaping on the pulp molding machine, and finally obtains a paper product with a specific geometric cavity structure.

[0004] Since the main principle component of pulp molded products is cellulose, there are a lot of gap structures in its fiber network, which has the defects of easy chip shedding and poor waterproof performance, and cannot fully meet the performance requirements of fast food tableware, etc. In the prior art, the waterproof performance of pulp molded products is improved by using plasticizers in the form of internal sizing or surface sizing.

[0005] Existing plasticizers are used in the preparation of pulp molding. Although they can prevent pulp molding from dropping and improve the waterproof performance of pulp molding to a certain extent, the plasticizers used will affect the mechanical properties of pulp molding, directly leading to poor strength and stiffness of pulp molding. At the same time, the plasticizer has poor bonding performance with pulp molding materials, and the poor bonding performance between the plasticizer and the outer surface of the fiber leads to weak waterproofness of the pulp molding material. At the same time, the plasticizer has poor stability in the gaps of the fiber network. During long-term use or exposed storage, the waterproof performance and physical properties of the pulp molded products are reduced, and the waterproof performance and physical properties cannot be maintained as they should be.

[0006] Furthermore, the existing plasticizers have poor emulsion stability. If improperly preserved or stored for a long time, the plasticizers are prone to failure, which directly leads to a reduction in the performance improvement effect on pulp molding. Summary of the invention

[0007] In order to solve the technical problems existing in the prior art, the present invention provides a hot water penetration resistant plasticizer, a preparation method and an application in paper mold manufacturing, which can avoid pulp molding chipping, effectively improve the waterproof performance of pulp molding, effectively avoid the influence of the plasticizer on the mechanical properties of pulp molding, and further improve the strength and stiffness of pulp molding; at the same time, improve the bonding performance of the plasticizer and the pulp molding material, improve the overall stability of the pulp molded product; and further improve the long-term storage stability of the plasticizer.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a hot water-permeable plastic film agent comprises the following steps: preparing a reaction base material, preparing a dropping liquid, and contact reaction.

[0010] The method for preparing the reaction base material comprises the following steps: adding methacryloyloxyethyl trimethylammonium chloride DMC, methyl methacrylate and vinyl propionate into a reaction kettle, mixing them evenly, adding azobisisobutyronitrile, stirring and heating to 80-85° C., keeping the temperature for polymerization for 2-3 hours, adding deionized water and adjusting the pH to 5-6, then adding a reinforcing modifier, stirring for 20-30 minutes, and obtaining the reaction base material.

[0011] In the preparation of the reaction base material, the weight ratio of methacryloyloxyethyl trimethyl ammonium chloride DMC, methyl methacrylate, vinyl propionate, azobisisobutyronitrile, deionized water, and reinforcing modifier is 18-20:80-85:2-2.5:0.2-0.23:105-110:14-15.

[0012] The reinforcing modifier is prepared by the following steps: preparing a composite, aldehyde treatment, and hyperbranching treatment;

[0013] The method for preparing the composite comprises the following steps: adding zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid and polyvinyl pyrrolidone into N,N-dimethylformamide (DMF), stirring for 10-20 minutes, adding nano silicon dioxide with an average particle size of 10-20 nm, and ultrasonically dispersing for 5-10 minutes to obtain a mixed dispersion; then placing the mixed dispersion in a high-pressure reactor, sealing the high-pressure reactor, placing the high-pressure reactor in a constant temperature box, heating to 120-125° C., keeping the temperature for reaction for 22-24 hours, and cooling naturally; obtaining a solid by centrifugation, washing it 2-3 times with deionized water of 4-5 times its weight, and drying it at 105-115° C. for 10-12 hours to obtain the composite.

[0014] In the prepared composite, the weight ratio of zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid, polyvinyl pyrrolidone, N,N-dimethylformamide DMF and nano silicon dioxide is 10-11:3-3.3:8.2-8.6:6.5-7:330-350:60-65.

[0015] The method for the aldehyde treatment is as follows: the composite is put into an ethanol solution (volume concentration of 85-90%) of 5-6 times its weight, stirred for 10-20 minutes, and then anhydrous acetic acid is used to adjust the pH to 5-5.5, stirred and heated to 35-40° C., and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is added dropwise while maintaining the temperature and stirring; and the addition time of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is controlled to be 60-90 minutes; N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is added dropwise to the ethanol solution of 5-6 times its weight, and then the ethanol solution is stirred for 10-20 minutes. After the addition of methoxysilane is completed, the mixture is stirred at a temperature of 4-5 hours, the solid is separated, washed with 3-4 times the weight of deionized water, and dried at 105-115° C. for 7-8 hours to obtain a modified intermediate; the modified intermediate is then added to 9-10 times the weight of a glutaraldehyde aqueous solution (mass concentration 1.2-1.5wt%), stirred at room temperature for 2-3 hours, the solid is separated, washed with 4-5 times the weight of deionized water, and dried at 105-115° C. to constant weight to obtain an aldehyde-modified product.

[0016] In the aldehyde treatment, the weight ratio of the composite to N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 1:0.2-0.23.

[0017] The hyperbranching treatment method comprises the following steps: putting the aldehyde modified substance into a reaction kettle containing anhydrous ethanol, stirring for 20-30 minutes, completely replacing the air in the reaction kettle with nitrogen, then stirring and heating to 65-70° C., dripping a hyperbranching treatment liquid while keeping the temperature and stirring, and controlling the dripping time of the hyperbranching treatment liquid to be 2-3 hours; after the hyperbranching treatment liquid is dripped, keeping the temperature and stirring for 2-3 hours, naturally cooling to room temperature, separating out the solid, washing it 2-3 times with 4-5 times the weight of anhydrous ethanol, placing it in a vacuum drying oven, and drying it at 30-35° C. for 22-24 hours in a vacuum environment of 0.085-0.095 MPa to obtain a reinforcing modifier.

[0018] In the hyperbranching treatment, the weight ratio of the aldehyde modified substance to anhydrous ethanol is 1:3-4;

[0019] The hyperbranched treatment liquid is an ethanol solution of dendritic polyamide-amine PAMAM; the mass concentration of the dendritic polyamide-amine is 8-8.5wt%, and the volume concentration of the ethanol solution is 50-55%;

[0020] The weight ratio of the aldehyde modified product to the dendritic polyamidoamine in the hyperbranched treatment solution is 1:0.25-0.3.

[0021] The method for preparing the drop-adding liquid comprises the following steps: adding styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyl dimethyl ammonium chloride and deionized water into a first ingredient kettle, stirring for 10-20 minutes, and then adding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate, stirring and emulsifying for 30-40 minutes to obtain a first drop-adding liquid for standby use; adding sodium sulfite and deionized water into a second ingredient kettle, stirring and dissolving to obtain a second drop-adding liquid for standby use.

[0022] In the preparation of the dropwise solution, in the first dropwise solution, the weight ratio of styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyldimethylammonium chloride, deionized water, and lauryl alcohol polyoxyethylene ether sulfosuccinic acid disodium salt is 45-50:4.5-5:2.3-2.5:7-8:80-85:0.8-1.2.

[0023] In the second drop of liquid, the weight ratio of sodium sulfite to deionized water is 6-6.5:100.

[0024] The contact reaction method comprises the following steps: stirring and heating the reaction base material to 85-90° C., dripping the first droplet and the second droplet into the reaction base material simultaneously, and controlling the dripping rate of the first droplet to be 6-7 mL / min and the dripping rate of the second droplet to be 0.5-0.6 mL / min; after the dripping of the first droplet is completed, stopping the dripping of the second droplet, keeping the temperature for reaction for 2-3 hours, and naturally cooling to room temperature to obtain a hot water-permeable plastic film agent.

[0025] In the contact reaction, the weight ratio of the reaction base material to the first drop liquid is 100:75-80.

[0026] A hot water-penetration-resistant plastic film agent is prepared by the above-mentioned preparation method.

[0027] Application of a hot water-proof plastic film agent in paper mold manufacturing, wherein the hot water-proof plastic film agent is mixed with a pulp molding slurry to prepare the pulp molding;

[0028] Wherein, the added amount of the hot water penetration-proof plasticizer is 1.5-1.8% of the weight of the pulp molding slurry.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The method for preparing a hot water penetration resistant plastic film agent of the present invention comprises the following steps: in the step of preparing a reaction base material, a cationic monomer methacryloyloxyethyl trimethyl ammonium chloride DMC, an acrylate monomer methyl methacrylate, and a nonionic monomer vinyl propionate are used to initiate prepolymerization in the presence of azobisisobutyronitrile, and then the prepolymer is uniformly mixed with a reinforcing modifier to obtain a reaction base material; in the preparation of the reinforcing modifier, nano-silica is used as a matrix, and a zinc-doped zirconium-based metal organic framework is compounded with the nano-silica by an in-situ generation method to obtain a composite; in the step of aldehyde treatment, a specific bisaminosilane is first used to perform an amine treatment on the composite; A modified intermediate is prepared by aldehyde treatment, and then the modified intermediate is subjected to aldehyde modification treatment with glutaraldehyde to obtain an aldehyde modified product; in the hyperbranching treatment step, the aldehyde modified product is further subjected to hyperbranching modification treatment with a dendritic polyamide-amine PAMAM to obtain a reinforcing modifier; then in the step of preparing a drop solution, a styrene monomer, a functional acrylate monomer, a cross-linking monomer, and a cationic monomer are prepared by dispersion and emulsification to obtain a first drop solution; and a second drop solution containing an oxidant is prepared; and then in the contact reaction step, a contact reaction is carried out by simultaneously dropping the first drop solution and the second drop solution; In this process, the reinforcing modifier forms more cross-linking points with the polymer components through the surface side chains and end groups, thereby improving the stability and weather resistance of the plasticizer, improving the long-term storage stability of the plasticizer, and avoiding possible microphase separation of the plasticizer; in the subsequent application of the plasticizer, the mechanical properties of the pulp molding are further improved by the reinforcing modifier and the fiber in the pulp molding and its filling effect on the pores of the fiber network in the pulp molding. While exerting physical barrier properties to prevent water penetration, the reinforcing modifier and the polymer form a dense cross-linking network in the pulp molding raw material, thereby forming a dense waterproof coating, thereby improving the plasticizer. The above-mentioned technical means cooperate with each other and work synergistically to avoid pulp molding chip shedding, effectively improve the waterproof performance of pulp molding, effectively avoid the influence of plasticizer on the mechanical properties of pulp molding, and further improve the strength and stiffness of pulp molding; at the same time, improve the bonding performance of plasticizer and pulp molding materials, improve the overall stability of pulp molded products; and further improve the long-term storage stability of plasticizer.

[0031] (2) The hot water penetration resistant plasticizer of the present invention, after being mixed with the pulp molding slurry, has a beating degree of 23.9-24.1°SR and a water retention value of 1.77-1.79 g / g; after the hot water penetration resistant plasticizer is mixed with the pulp molding slurry, the pulp molded product obtained has no powder or crumb drop, and the pulp molded product (thickness 0.8 mm, basis weight 400 g / m2 ) has a tensile strength of 99.2-99.5Nm / g and a burst index of 4.3-4.4 (kPa·m 2 ) / g, tightness is 1.38-1.41g / cm 3 , tear strength is 6.74-6.79 (mN·m 2 ) / g.

[0032] (3) The hot water penetration-proof plasticizer of the present invention is mixed with a pulp molding slurry to prepare a pulp molding product (thickness 0.8 mm, basis weight 400 g / m 2 The Cobb value (120s) is 12.4-12.7g / m 2 The water contact angle is 121-122°; 100°C hot water is left on the pulp molding surface for 70 minutes, and no hot water penetrates or diffuses.

[0033] (4) The hot water penetration-proof plasticizer of the present invention is mixed with a pulp molding slurry to prepare a pulp molding product (thickness 0.8 mm, basis weight 400 g / m 2 ) After 270 days of storage in an environment with a temperature of 30°C and a relative humidity of 75%, there was no detachment or damage to the waterproof film layer on the outer surface of the fiber in the pulp molding. The tensile strength of the pulp molding product was 98.8-99.3Nm / g, and the burst index was 4.3-4.4 (kPa·m 2 ) / g, tightness is 1.36-1.39g / cm 3 , tear strength is 6.68-6.74 (mN·m 2 ) / g, Cobb value (120s) is 13.5-13.9g / m 2 The water contact angle is 120-121°; 100°C hot water is left on the pulp molding surface for 70 minutes, and no hot water penetrates or diffuses.

[0034] (5) After being stored for 180 days in an environment with a temperature of 35°C and a relative humidity of 85%, the hot water penetration resistant plasticizer of the present invention has no delamination or precipitation. The pulp molded products (thickness 0.8 mm, basis weight 400 g / m 2 ) has a tensile strength of 96.2-96.6Nm / g and a burst index of 4.2-4.3 (kPa·m 2 ) / g, tightness is 1.33-1.36g / cm 3 , tear strength is 6.54-6.59 (mN·m 2 ) / g, Cobb value (120s) is 12.8-13.1g / m 2The water contact angle is 119-120°; 100°C hot water is left on the pulp molding surface for 70 minutes, and no hot water penetrates or diffuses. DETAILED DESCRIPTION

[0035] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0036] Example 1

[0037] This embodiment provides a method for preparing a hot water-proof plastic film agent, which comprises the following steps:

[0038] 1. Prepare reaction base

[0039] Methacryloyloxyethyltrimethylammonium chloride DMC, methyl methacrylate and vinyl propionate are added into a reactor, mixed evenly, and then azobisisobutyronitrile is added. The mixture is stirred and heated to 80°C. After heat preservation and polymerization for 2 hours, deionized water is added and the pH is adjusted to 5. Then, a reinforcing modifier is added. After stirring for 20 minutes, a reaction base material is obtained.

[0040] Among them, the weight ratio of methacryloyloxyethyltrimethylammonium chloride DMC, methyl methacrylate, vinyl propionate, azobisisobutyronitrile, deionized water, and reinforcing modifier is 18:80:2:0.2:105:14.

[0041] The reinforcing modifier is prepared by the following method:

[0042] 1) Preparation of complex

[0043] Zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid and polyvinyl pyrrolidone are added to N,N-dimethylformamide (DMF), stirred for 10 minutes, and then nano-silicon dioxide with an average particle size of 10 nm is added, and ultrasonic dispersion is performed for 5 minutes to obtain a mixed dispersion; the mixed dispersion is then placed in a high-pressure reactor, and the high-pressure reactor is sealed and placed in a constant temperature box, heated to 120°C, kept warm for reaction for 22 hours, and then naturally cooled; after obtaining a solid by centrifugation, it is washed twice with 4 times the weight of deionized water, and dried at 105°C for 10 hours to obtain a composite.

[0044] Among them, the weight ratio of zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid, polyvinyl pyrrolidone, N,N-dimethylformamide DMF and nano-silicon dioxide is 10:3:8.2:6.5:330:60.

[0045] 2) Aldehydation treatment

[0046] The complex was added to 5 times the weight of an ethanol solution (volume concentration of 85%), stirred for 10 minutes, and then the pH was adjusted to 5 with anhydrous acetic acid. The temperature was raised to 35°C with stirring, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added dropwise with stirring while keeping the temperature constant. The addition time of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was controlled to be 60 minutes. After the addition of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was completed, the mixture was kept warm and stirred for 4 hours, and the solid was separated. After washing with 3 times the weight of deionized water, the solid was dried at 105°C for 7 hours to obtain a modified intermediate. The modified intermediate was then added to 9 times the weight of a glutaraldehyde aqueous solution (mass concentration of 1.2wt%), stirred at room temperature for 2 hours, and the solid was separated. After washing with 4 times the weight of deionized water, the solid was dried at 105°C to constant weight to obtain an aldehyde-modified product.

[0047] The weight ratio of the composite to N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 1:0.2.

[0048] 3) Hyperbranching treatment

[0049] The aldehyde modified product was put into a reactor filled with anhydrous ethanol, and after stirring for 20 minutes, the air in the reactor was completely replaced by nitrogen, and then the temperature was raised to 65°C with stirring, and the hyperbranched treatment liquid was added dropwise with insulation and stirring, and the addition time of the hyperbranched treatment liquid was controlled to be 2 hours; after the hyperbranched treatment liquid was added dropwise, the insulation and stirring were continued for 2 hours, and the product was naturally cooled to room temperature, and the solid was separated, washed twice with 4 times the weight of anhydrous ethanol, and dried to obtain a reinforcing modifier.

[0050] The weight ratio of the aldehyde modified product to anhydrous ethanol is 1:3.

[0051] The hyperbranched treatment liquid is an ethanol solution of dendritic polyamide-amine PAMAM; the mass concentration of the dendritic polyamide-amine is 8wt%, and the volume concentration of the ethanol solution is 50%.

[0052] The weight ratio of the aldehyde modified product to the dendritic polyamidoamine in the hyperbranched treatment solution is 1:0.25.

[0053] 2. Preparation of dropping solution

[0054] Styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyl dimethyl ammonium chloride and deionized water are added into a first ingredient kettle, stirred for 10 minutes, and then disodium lauryl polyoxyethylene ether sulfosuccinate is added, stirred and emulsified for 30 minutes to obtain a first drop solution for standby use; sodium sulfite and deionized water are added into a second ingredient kettle, stirred and dissolved to obtain a second drop solution for standby use.

[0055] Among them, in the first drop liquid, the weight ratio of styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyldimethylammonium chloride, deionized water, and lauryl alcohol polyoxyethylene ether sulfosuccinic acid disodium salt is 45:4.5:2.3:7:80:0.8.

[0056] In the second drop of liquid, the weight ratio of sodium sulfite to deionized water is 6:100.

[0057] 3. Contact reaction

[0058] The reaction base material was stirred and heated to 85°C, and the first drop liquid and the second drop liquid were simultaneously added dropwise to the reaction base material, and the dropping rate of the first drop liquid was controlled to be 6 mL / min, and the dropping rate of the second drop liquid was controlled to be 0.5 mL / min; after the first drop liquid was added dropwise, the second drop liquid was stopped, and the reaction was kept warm for 2 hours, and then naturally cooled to room temperature to obtain a plastic film agent that is resistant to hot water penetration.

[0059] Wherein, the weight ratio of the reaction base material to the first drop liquid is 100:75.

[0060] After product qualification test, the effective ingredient content of the hot water penetration resistant plastic film of this embodiment is greater than 21wt%, and the density (25℃) is less than 1.08g / cm 3 , viscosity (25℃) ≤50mPa·s, pH (25℃) in the range of 3.0-6.0, can be mixed with water in any proportion.

[0061] This embodiment also provides a hot water-permeable plasticizer, which is prepared by the aforementioned preparation method.

[0062] This embodiment also provides an application of a hot water-proof plastic film agent in paper mold manufacturing. The hot water-proof plastic film agent is mixed with a pulp molding slurry to prepare the pulp molding.

[0063] Wherein, the added amount of the hot water penetration-proof plasticizer is 1.6% of the weight of the pulp molding slurry.

[0064] Example 2

[0065] This embodiment provides a method for preparing a hot water-proof plastic film agent, which comprises the following steps:

[0066] 1. Prepare reaction base

[0067] Methacryloyloxyethyltrimethylammonium chloride DMC, methyl methacrylate and vinyl propionate are added into a reactor, mixed evenly, and then azobisisobutyronitrile is added. The mixture is stirred and heated to 82°C. After heat preservation and polymerization for 2.5 hours, deionized water is added and the pH is adjusted to 5.5. Then, a reinforcing modifier is added. After stirring for 25 minutes, a reaction base material is obtained.

[0068] Among them, the weight ratio of methacryloyloxyethyltrimethylammonium chloride DMC, methyl methacrylate, vinyl propionate, azobisisobutyronitrile, deionized water, and reinforcing modifier is 19:83:2.2:0.21:107:14.6.

[0069] The reinforcing modifier is prepared by the following method:

[0070] 1) Preparation of complex

[0071] Zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid and polyvinyl pyrrolidone are added to N,N-dimethylformamide (DMF), stirred for 15 minutes, and then nano-silicon dioxide with an average particle size of 15 nm is added, and ultrasonic dispersion is performed for 8 minutes to obtain a mixed dispersion; the mixed dispersion is then placed in a high-pressure reactor, and the high-pressure reactor is sealed and placed in a constant temperature box, heated to 123°C, kept warm for reaction for 23 hours, and then naturally cooled; after obtaining a solid by centrifugation, it is washed three times with 4.5 times the weight of deionized water, and dried at 110°C for 11 hours to obtain a composite.

[0072] Among them, the weight ratio of zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid, polyvinyl pyrrolidone, N,N-dimethylformamide DMF and nano-silicon dioxide is 10.5:3.2:8.5:6.7:340:62.

[0073] 2) Aldehydation treatment

[0074] The complex was added to 5.5 times the weight of an ethanol solution (volume concentration of 87%), stirred for 15 minutes, and then the pH was adjusted to 5.2 with anhydrous acetic acid. The temperature was raised to 38°C with stirring, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added dropwise with stirring while keeping the temperature constant. The addition time of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was controlled to be 80 minutes. After the addition of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was completed, the mixture was kept warm and stirred for 4.5 hours, and the solid was separated. After washing with 3.5 times the weight of deionized water, the solid was dried at 110°C for 7.5 hours to obtain a modified intermediate. The modified intermediate was then added to 9.5 times the weight of a glutaraldehyde aqueous solution (mass concentration of 1.3wt%), stirred at room temperature for 2.5 hours, and the solid was separated. After washing with 4.5 times the weight of deionized water, the solid was dried at 110°C to constant weight to obtain an aldehyde-modified product.

[0075] The weight ratio of the composite to N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 1:0.22.

[0076] 3) Hyperbranching treatment

[0077] The aldehyde modified product was put into a reactor filled with anhydrous ethanol, and after stirring for 25 minutes, the air in the reactor was completely replaced by nitrogen, and then the temperature was raised to 68°C with stirring, and the hyperbranched treatment liquid was added dropwise with insulation and stirring, and the addition time of the hyperbranched treatment liquid was controlled to be 2.5 hours; after the hyperbranched treatment liquid was added dropwise, the insulation and stirring were continued for 2.5 hours, and the product was naturally cooled to room temperature, and the solid was separated, washed three times with 4.5 times the weight of anhydrous ethanol, and dried to obtain a reinforcing modifier.

[0078] The weight ratio of the aldehyde modified product to anhydrous ethanol is 1:3.5.

[0079] The hyperbranched treatment liquid is an ethanol solution of dendritic polyamide-amine PAMAM; the mass concentration of the dendritic polyamide-amine is 8.2wt%, and the volume concentration of the ethanol solution is 52%.

[0080] The weight ratio of the aldehyde modified product to the dendritic polyamidoamine in the hyperbranched treatment solution is 1:0.28.

[0081] 2. Preparation of dropping solution

[0082] Styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyl dimethyl ammonium chloride and deionized water are added into a first ingredient kettle, stirred for 15 minutes, and then disodium lauryl polyoxyethylene ether sulfosuccinate is added, stirred and emulsified for 35 minutes to obtain a first drop solution for standby use; sodium sulfite and deionized water are added into a second ingredient kettle, stirred and dissolved to obtain a second drop solution for standby use.

[0083] Among them, in the first drop liquid, the weight ratio of styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyldimethylammonium chloride, deionized water, and lauryl alcohol polyoxyethylene ether sulfosuccinic acid disodium salt is 48:4.7:2.4:7.5:82:1.1.

[0084] In the second drop of liquid, the weight ratio of sodium sulfite to deionized water is 6.2:100.

[0085] 3. Contact reaction

[0086] The reaction base material was stirred and heated to 88°C, and the first drop liquid and the second drop liquid were simultaneously added dropwise to the reaction base material, and the dropping rate of the first drop liquid was controlled to be 6.5 mL / min, and the dropping rate of the second drop liquid was controlled to be 0.55 mL / min; after the first drop liquid was added dropwise, the second drop liquid was stopped, and the reaction was kept warm for 2.5 hours, and then naturally cooled to room temperature to obtain a plastic film agent that is resistant to hot water penetration.

[0087] Wherein, the weight ratio of the reaction base material to the first drop liquid is 100:77.

[0088] After product qualification test, the effective ingredient content of the hot water penetration resistant plastic film of this embodiment is greater than 21wt%, and the density (25℃) is less than 1.08g / cm 3 , viscosity (25℃) ≤50mPa·s, pH (25℃) in the range of 3.0-6.0, can be mixed with water in any proportion.

[0089] This embodiment also provides a hot water-permeable plasticizer, which is prepared by the aforementioned preparation method.

[0090] This embodiment also provides an application of a hot water-proof plastic film agent in paper mold manufacturing. The hot water-proof plastic film agent is mixed with a pulp molding slurry to prepare the pulp molding.

[0091] Wherein, the added amount of the hot water penetration-proof plasticizer is 1.6% of the weight of the pulp molding slurry.

[0092] Example 3

[0093] This embodiment provides a method for preparing a hot water-proof plastic film agent, which comprises the following steps:

[0094] 1. Prepare reaction base

[0095] Methacryloyloxyethyltrimethylammonium chloride DMC, methyl methacrylate and vinyl propionate are added into a reactor, mixed evenly, and then azobisisobutyronitrile is added. The mixture is stirred and heated to 85°C. After heat preservation and polymerization for 3 hours, deionized water is added and the pH is adjusted to 6. Then, a reinforcing modifier is added. After stirring for 30 minutes, a reaction base material is obtained.

[0096] Among them, the weight ratio of methacryloyloxyethyltrimethylammonium chloride DMC, methyl methacrylate, vinyl propionate, azobisisobutyronitrile, deionized water, and reinforcing modifier is 20:85:2.5:0.23:110:15.

[0097] The reinforcing modifier is prepared by the following method:

[0098] 1) Preparation of complex

[0099] Zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid and polyvinyl pyrrolidone are added to N,N-dimethylformamide (DMF), stirred for 20 minutes, and then nano-silicon dioxide with an average particle size of 20 nm is added, and ultrasonic dispersion is performed for 10 minutes to obtain a mixed dispersion; the mixed dispersion is then placed in a high-pressure reactor, and the high-pressure reactor is sealed and placed in a constant temperature box, heated to 125°C, kept warm for reaction for 24 hours, and then naturally cooled; after obtaining a solid by centrifugation, it is washed three times with 5 times the weight of deionized water, and dried at 115°C for 12 hours to obtain a composite.

[0100] Among them, the weight ratio of zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid, polyvinyl pyrrolidone, N,N-dimethylformamide DMF and nano-silicon dioxide is 11:3.3:8.6:7:350:65.

[0101] 2) Aldehydation treatment

[0102] The complex was added to 6 times the weight of an ethanol solution (volume concentration of 90%), stirred for 20 minutes, and then the pH was adjusted to 5.5 with anhydrous acetic acid. The temperature was raised to 40°C with stirring, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added dropwise with stirring while keeping the temperature constant. The addition time of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was controlled to be 90 minutes. After the addition of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was completed, the mixture was kept warm and stirred for 5 hours, and the solid was separated. After washing with 4 times the weight of deionized water, the solid was dried at 115°C for 8 hours to obtain a modified intermediate. The modified intermediate was then added to 10 times the weight of a glutaraldehyde aqueous solution (mass concentration of 1.5wt%), stirred at room temperature for 3 hours, and the solid was separated. After washing with 5 times the weight of deionized water, the solid was dried at 115°C to constant weight to obtain an aldehyde-modified product.

[0103] The weight ratio of the composite to N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 1:0.23.

[0104] 3) Hyperbranching treatment

[0105] The aldehyde modified product was put into a reactor filled with anhydrous ethanol, and after stirring for 30 minutes, the air in the reactor was completely replaced by nitrogen, and then the temperature was raised to 70°C with stirring, and the hyperbranched treatment liquid was added dropwise with insulation and stirring, and the addition time of the hyperbranched treatment liquid was controlled to be 3 hours; after the hyperbranched treatment liquid was added dropwise, the insulation and stirring were continued for 3 hours, and the product was naturally cooled to room temperature, and the solid was separated, washed 3 times with 5 times the weight of anhydrous ethanol, and dried to obtain a reinforcing modifier.

[0106] The weight ratio of the aldehyde modified product to anhydrous ethanol is 1:4.

[0107] The hyperbranched treatment liquid is an ethanol solution of dendritic polyamide-amine PAMAM; the mass concentration of the dendritic polyamide-amine is 8.5wt%, and the volume concentration of the ethanol solution is 55%.

[0108] The weight ratio of the aldehyde modified product to the dendritic polyamidoamine in the hyperbranched treatment solution is 1:0.3.

[0109] 2. Preparation of dropping solution

[0110] Styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyl dimethyl ammonium chloride and deionized water are added into a first ingredient kettle, stirred for 20 minutes, and then disodium lauryl polyoxyethylene ether sulfosuccinate is added, stirred and emulsified for 40 minutes to obtain a first drop solution for standby use; sodium sulfite and deionized water are added into a second ingredient kettle, stirred and dissolved to obtain a second drop solution for standby use.

[0111] Among them, in the first drop liquid, the weight ratio of styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyldimethylammonium chloride, deionized water, and lauryl alcohol polyoxyethylene ether sulfosuccinic acid disodium salt is 50:5:2.5:8:85:1.2.

[0112] In the second drop of liquid, the weight ratio of sodium sulfite to deionized water is 6.5:100.

[0113] 3. Contact reaction

[0114] The reaction base material was stirred and heated to 90°C, and the first drop liquid and the second drop liquid were simultaneously added dropwise to the reaction base material, and the dropping rate of the first drop liquid was controlled to be 7 mL / min, and the dropping rate of the second drop liquid was controlled to be 0.6 mL / min; after the first drop liquid was added dropwise, the second drop liquid was stopped, and the reaction was kept warm for 3 hours, and then naturally cooled to room temperature to obtain a plastic film agent that is resistant to hot water penetration.

[0115] The weight ratio of the reaction base material to the first drop of liquid is 100:80.

[0116] After product qualification test, the effective ingredient content of the hot water penetration resistant plastic film of this embodiment is greater than 21wt%, and the density (25℃) is less than 1.08g / cm 3 , viscosity (25℃) ≤50mPa·s, pH (25℃) in the range of 3.0-6.0, can be mixed with water in any proportion.

[0117] This embodiment also provides a hot water-permeable plasticizer, which is prepared by the aforementioned preparation method.

[0118] This embodiment also provides an application of a hot water-proof plastic film agent in paper mold manufacturing. The hot water-proof plastic film agent is mixed with a pulp molding slurry to prepare the pulp molding.

[0119] Wherein, the added amount of the hot water penetration-proof plasticizer is 1.6% of the weight of the pulp molding slurry.

[0120] Comparative Example 1

[0121] The technical solution of Example 2 is adopted, but the differences are: 1) in the step of preparing the reaction base material, the addition of vinyl propionate is omitted; 2) the step of preparing the composite is omitted, and nano-silica of the same specification is directly used in the aldehyde treatment step.

[0122] Comparative Example 2

[0123] The technical scheme of Example 2 is adopted, but the differences are as follows: 1) the hyperbranching treatment step is omitted, and the aldehyde modified product obtained in the previous step is used as a reinforcing modifier in the step of preparing the reaction base material; 2) in the step of preparing the dropping liquid, the addition of isooctyl acrylate and diallyldimethylammonium chloride in the first dropping liquid is omitted.

[0124] The amount of the hot water penetration-proof plasticizer added was controlled to be 1.6% of the weight of the pulp molding slurry. The hot water penetration-proof plasticizers of Examples 1-3 and Comparative Examples 1-2 were respectively used and mixed with the pulp molding slurry to prepare pulp molding to form a 0.8 mm thick, 400 g / m 2 Pulp molded products.

[0125] In the preparation process of pulp molding, the beating degree and water retention value of the slurry after each hot water penetration-proof plastic film agent is mixed with the pulp molding slurry are tested. At the same time, the prepared pulp molded products are placed in an environment with a temperature of 25°C and a relative humidity of 50%. After standing for 24 hours, the pulp molded products are observed to see if there is powder or crumb drop, and the tensile strength, bursting index, tightness, and tear strength of each pulp molded product are tested.

[0126] At the same time, the water absorption, wetting and hot water penetration resistance of pulp molded products are tested.

[0127] Among them, the detection of pulp beating degree refers to the standard GB / T 3332-2004 "Determination of pulp beating degree" (Schober-Riegle method).

[0128] For the detection of water retention value of pulp, refer to the standard GB / T 29286-2012 "Determination of water retention value of pulp".

[0129] For the testing of tensile strength, bursting index, tightness and tear strength of pulp molded products, refer to the standards GB / T12914-2018 "Determination of tensile strength of paper and paperboard - Constant tension method (20 mm / min)", GB / T 454-2020 "Determination of bursting resistance of paper", and GB / T 455-2002 "Determination of tear resistance of paper and paperboard".

[0130] The water absorption performance of pulp molded products is tested with reference to the standard GB / T1540-2002 "Determination of water absorption of paper and paperboard (Cobb method)". The Cobb value of each pulp molded product is tested using a Cobb water absorption tester; and the water absorption test time is set to 120s.

[0131] The wetting properties of pulp molded products were tested by cutting each pulp molded product into flat specimens of 10 mm × 15 mm in size, fixing them on a glass slide with double-sided tape, and measuring the water contact angle of deionized water on the outer surface of each specimen using a contact angle tester.

[0132] The hot water penetration resistance of pulp molded products is tested with reference to the standard GB / T 36787-2018 "Pulp Molded Tableware". Specifically, 100°C hot water is sucked up with a glass straw and dripped into each pulp molded product. The product is left to stand for 70 minutes to observe whether hot water penetration occurs in each pulp molded product.

[0133] The specific results are shown in the following table:

[0134]

[0135] Furthermore, pulp molded products (thickness 0.8 mm, basis weight 400 g / m 2 ) were placed in an environment with a temperature of 30°C and a relative humidity of 75%. After being exposed and stored for 270 days, the pulp molded products were observed to see if the waterproof film layer on the outer surface of the fiber in the pulp molding was detached or damaged; and the tensile strength, bursting index, tightness, tear strength, water absorption performance, wetting performance and hot water penetration resistance of each pulp molded product were tested respectively. The specific results are shown in the following table:

[0136]

[0137] Furthermore, the hot water penetration resistant plastic film agents of Examples 1-3 and Comparative Examples 1-2 were placed in an environment at a temperature of 35° C. and a relative humidity of 85% and stored for 180 days to observe whether the hot water penetration resistant plastic film agents were stratified or precipitated. The hot water penetration resistant plastic film agents were used to prepare pulp molded products. The obtained pulp molded products (thickness of 0.8 mm, basis weight of 400 g / m 2 ) were placed in an environment with a temperature of 25°C and a relative humidity of 50%. After standing for 24 hours, the tensile strength, bursting index, tightness and tear strength of each pulp molded product were tested; and the water absorption performance, wetting performance and hot water penetration resistance of each pulp molded product were tested.

[0138] The specific results are shown in the following table:

[0139]

[0140] It can be seen that the preparation method of the hot water penetration resistant plastic film agent of the present invention comprises the following steps: in the step of preparing the reaction base material, a cationic monomer methacryloyloxyethyl trimethyl ammonium chloride DMC, an acrylate monomer methyl methacrylate, and a nonionic monomer vinyl propionate are used to initiate prepolymerization in the presence of azobisisobutyronitrile, and then the prepolymer is uniformly mixed with a reinforcing modifier to obtain a reaction base material; in the preparation of the reinforcing modifier, nano-silica is used as a matrix, and a zinc-doped zirconium-based metal organic framework is compounded with nano-silica by an in-situ generation method to obtain a composite; in the step of aldehyde treatment, a specific bisaminosilane is first used to treat the composite material. The modified intermediate is subjected to an amination treatment, and then the modified intermediate is subjected to an aldehyde modification treatment using glutaraldehyde to obtain an aldehyde modified product; in the hyperbranching treatment step, the aldehyde modified product is further subjected to a hyperbranching modification treatment using a dendritic polyamide-amine PAMAM to obtain a reinforcing modifier; then in the step of preparing a drop solution, a styrene monomer, a functional acrylate monomer, a cross-linking monomer, and a cationic monomer are prepared by dispersion and emulsification to obtain a first drop solution; and a second drop solution containing an oxidant is prepared; and then in the step of contact reaction, the first drop solution and the second drop solution are simultaneously added dropwise to carry out a contact reaction. ; In this process, the reinforcing modifier forms more cross-linking points with the polymer components through the surface side chains and end groups, thereby improving the stability and weather resistance of the plastic film agent, improving the long-term storage stability of the plastic film agent, and avoiding possible microphase separation of the plastic film agent; in the subsequent application process of the plastic film agent, the mechanical properties of the pulp molding are further improved by the reinforcing modifier and the fiber in the pulp molding and its filling effect on the pores of the fiber network in the pulp molding. While exerting physical barrier properties to prevent water penetration, the reinforcing modifier and the polymer are combined to form a dense cross-linking network in the pulp molding raw material, thereby forming a dense waterproof coating, thereby improving the plastic film The invention relates to a novel method for improving the bonding performance of the plasticizer with the fibers in pulp molding, enhancing the hydrophobicity of the fiber surface, and further improving the uniformity of film formation and the stability of the film layer of the plasticizer on the outer surface of the fiber in pulp molding, thereby improving the overall stability of pulp molding; the aforementioned technical means cooperate with each other and work synergistically, which can avoid the pulp molding from shedding, effectively improve the waterproof performance of pulp molding, and effectively avoid the influence of the plasticizer on the mechanical properties of pulp molding, further improve the strength and stiffness of pulp molding; at the same time, improve the bonding performance of the plasticizer with the pulp molding material, improve the overall stability of the pulp molded products; and further improve the long-term storage stability of the plasticizer.

[0141] It can be seen from Comparative Example 1 that after omitting the addition of non-ionic monomers and omitting the composite of zinc-doped zirconium-based metal-organic frameworks and nano-silica, it is impossible to form a more complex and continuous and dense waterproof polymer network structure through the interaction between non-ionic monomers and other raw material monomers (such as acrylate monomers, etc.); it is also impossible to further improve the interfacial bonding performance of the plastic film agent and the pulp molding material through the non-ionic monomers; at the same time, it is impossible to achieve the filling and barrier effect of the pulp molding pores through the combination of zinc-doped zirconium-based metal-organic frameworks and nano-silica, and it is impossible to avoid the possible microphase separation of the plastic film agent while further improving the mechanical properties and waterproof properties of the pulp molding, and improve the stability and weather resistance of the plastic film agent. It is impossible to effectively avoid the possible microphase separation of the plastic film agent and the long-term storage performance of the plastic film agent. Specifically, the water filtration performance of the pulp molding slurry is reduced during the preparation process, and the mechanical properties (tensile strength, bursting index, tightness, tear strength) and waterproof properties (120s Cobb value, water contact angle, hot water penetration resistance) of the prepared pulp molded products are reduced to a certain extent; and the overall stability of the prepared pulp molded products is reduced. After long-term exposed static storage, the mechanical properties and waterproof properties of the pulp molding are reduced to a certain extent; and after long-term storage of the plastic film agent, the mechanical properties (tensile strength, bursting index, tightness, tear strength) and waterproof properties (120s Cobb value, water contact angle, hot water penetration resistance) of the prepared pulp molded products are reduced to a certain extent.

[0142] It can be seen from Comparative Example 2 that after omitting the hyperbranching treatment step in the reinforcing modifier and omitting the addition of isooctyl acrylate and diallyldimethylammonium chloride in the first drop liquid, the aldehyde modified product that is only subjected to the aldehyde modification treatment has reduced binding performance with the polymer raw material in the plasticizer, and cannot effectively cooperate to improve the mechanical properties, waterproof properties and overall stability of the pulp molded product, nor can it improve the long-term storage performance of the plasticizer; and the waterproof performance of the plasticizer cannot be further improved by cooperating the functional acrylate monomer and the cationic monomer with other raw materials in the first drop liquid. Specifically, the water filtration performance of the pulp molding slurry is reduced during the preparation process, and the mechanical properties (tensile strength, bursting index, tightness, tear strength) and waterproof properties (120s Cobb value, water contact angle, hot water penetration resistance) of the prepared pulp molded products are significantly reduced; and the overall stability of the prepared pulp molded products is reduced. After long-term exposed static storage, the mechanical properties and waterproof properties of the pulp molding are significantly reduced; and after long-term storage of the plastic film agent, the mechanical properties (tensile strength, bursting index, tightness, tear strength) and waterproof properties (120s Cobb value, water contact angle, hot water penetration resistance) of the prepared pulp molded products are significantly reduced.

[0143] Unless otherwise specified, all percentages used in the present invention are by mass.

[0144] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hot water-proof plastic film, characterized in that: The method comprises the following steps: preparing a reaction base material, preparing a dropping liquid, and contacting and reacting; The method for preparing the reaction base material comprises: mixing methacryloyloxyethyl trimethylammonium chloride, methyl methacrylate and vinyl propionate uniformly, adding azobisisobutyronitrile, heating, keeping the temperature for polymerization, adjusting the pH to 5-6, adding a reinforcing modifier, mixing uniformly, and preparing the reaction base material; The reinforcing modifier is prepared by the following steps: preparing a composite, aldehyde treatment, and hyperbranching treatment; The method for preparing the composite comprises: adding zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid and polyvinyl pyrrolidone into N,N-dimethylformamide, mixing them evenly, adding nano silicon dioxide to obtain a mixed dispersion; placing the mixed dispersion in a high-pressure reactor, sealing the high-pressure reactor, heating it to 120-125° C., keeping the temperature for reaction, and separating to obtain a solid; washing and drying the solid to obtain the composite; The method for the aldehyde treatment comprises the following steps: putting the complex into an ethanol solution, mixing it evenly, adjusting the pH to 5-5.5, heating it to 35-40° C., and dropping N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane while keeping the temperature and stirring; after the dropping is completed, continuing to keep the temperature and stirring, separating out a solid, washing the solid, and drying the solid to obtain a modified intermediate; then putting the modified intermediate into a glutaraldehyde aqueous solution, stirring at room temperature, separating out a solid, and washing and drying the solid to obtain an aldehyde modified product; The hyperbranching treatment method comprises: adding the aldehyde modified substance into anhydrous ethanol, mixing evenly, heating to 65-70° C. in a nitrogen atmosphere, and dripping the hyperbranching treatment liquid while keeping the temperature and stirring; after the dripping is completed, continuing to keep the temperature and stirring, cooling to room temperature, separating the solid matter, washing the solid matter, and drying it to obtain the reinforcing modifier; The hyperbranched treatment liquid is an ethanol solution of dendritic polyamide-amine; The method for preparing the drop-adding liquid comprises: uniformly mixing styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyl dimethyl ammonium chloride and deionized water, adding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate, stirring and emulsifying to obtain a first drop-adding liquid; uniformly mixing sodium sulfite and deionized water to obtain a second drop-adding liquid; The contact reaction method is to simultaneously drop the first drop liquid and the second drop liquid into the reaction base material, and react to obtain a hot water-permeable plastic film agent.

2. The method for preparing a hot water penetration resistant plasticizer according to claim 1, characterized in that: In the preparation of the reaction base material, the heat preservation polymerization temperature is 80-85° C., and the heat preservation polymerization time is 2-3 hours; The weight ratio of methacryloyloxyethyl trimethylammonium chloride, methyl methacrylate, vinyl propionate, azobisisobutyronitrile, deionized water and reinforcing modifier is 18-20:80-85:2-2.5:0.2-0.23:105-110:14-15.

3. The method for preparing a hot water penetration resistant plasticizer according to claim 1, characterized in that: In the prepared composite, the average particle size of the nano-silicon dioxide is 10-20 nm; The reaction time at 120-125℃ is 22-24h; The weight ratio of zirconium nitrate pentahydrate, zinc nitrate hexahydrate, trimesic acid, polyvinyl pyrrolidone, N,N-dimethylformamide and nano silicon dioxide is 10-11:3-3.3:8.2-8.6:6.5-7:330-350:60-65.

4. The method for preparing a hot water penetration resistant plasticizer according to claim 1, characterized in that: In the aldehyde treatment, the weight ratio of the composite, the ethanol solution, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 1:5-6:0.2-0.23; The volume concentration of the ethanol solution is 85-90%; The addition time of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 60-90 min; The time of heat preservation and stirring after the dropwise addition of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 4-5 hours.

5. The method for preparing a hot water penetration resistant plasticizer according to claim 1, characterized in that: In the formylation treatment, the weight ratio of the modified intermediate to the aqueous solution of glutaraldehyde is 1:9-10; The mass concentration of the glutaraldehyde aqueous solution is 1.2-1.5wt%; The modified intermediate is stirred in the glutaraldehyde aqueous solution at room temperature for 2-3 hours.

6. The method for preparing a hot water penetration resistant plasticizer according to claim 1, characterized in that: In the hyperbranching treatment, the hyperbranching treatment solution is added dropwise for 2-3 hours; The heat preservation and stirring time after the hyperbranched treatment liquid is added is 2-3 hours; The weight ratio of the aldehyde modified substance to anhydrous ethanol is 1:3-4; In the hyperbranched treatment solution, the mass concentration of the dendritic polyamidoamine is 8-8.5wt%, and the volume concentration of the ethanol solution is 50-55%; The weight ratio of the aldehyde modified product to the dendritic polyamide amine in the hyperbranched treatment solution is 1:0.25-0.

3.

7. The method for preparing a hot water penetration resistant plasticizer according to claim 1, characterized in that: In the preparation of the dropwise solution, the weight ratio of styrene, isooctyl acrylate, ethylene glycol dimethacrylate, diallyldimethylammonium chloride, deionized water, and lauryl alcohol polyoxyethylene ether sulfosuccinic acid disodium salt in the first dropwise solution is 45-50:4.5-5:2.3-2.5:7-8:80-85:0.8-1.2; The weight ratio of sodium sulfite to deionized water in the second dropwise addition liquid is 6-6.5:

100.

8. The method for preparing a hot water penetration resistant plasticizer according to claim 1, characterized in that: The contact reaction method comprises the following steps: stirring the reaction base material and heating it to 85-90° C., simultaneously dropping the first droplet and the second droplet into the reaction base material, stopping the dropping of the second droplet after the first droplet is added, keeping the temperature for reaction for 2-3 hours, and cooling to obtain a hot water-resistant plastic film agent; The first droplet addition rate is 6-7 mL / min, and the second droplet addition rate is 0.5-0.6 mL / min; The weight ratio of the reaction base material to the first drop of liquid is 100:75-80.

9. A hot water-proof plasticizer, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. Application of a hot water-proof plasticizer in paper mold manufacturing, characterized in that: After mixing the hot water penetration-proof plasticizer of claim 9 with a pulp molding slurry, pulp molding is prepared; The amount of the hot water penetration-proof plasticizer added is 1.5-1.8% of the weight of the pulp molding slurry.

Citation Information

Patent Citations

  • Use of branched addition copolymers in curing systems

    CN102630232A

  • Modified nanometer graphite reinforced water-based fluorocarbon antirust coating material for vehicle chassis, and preparation method thereof

    CN106519871A